Factors Affecting Interest In Buying Tickets For Purwakarta's Sound Of Wibu 2.0 Event - Muhammad Rezarivaldy; Kristiana Widiawati (Universitas Indonesia Membangun (Inaba), 2026)
The increasing number of Japanese culture enthusiasts from teenagers to adults who regularly attend Japanese cultural events in Purwakarta is the driving force for this study. There is still a gap between the community's need for Japanese cultural events in the area and the actual number of visitors, despite this growing enthusiasm. Furthermore, more research is required due to discrepancies in earlier studies' conclusions about the variables impacting purchase intention. Based on marketing and marketing mix theories, this study attempts to examine how price, location, and service quality affect purchase intention. Purposive sampling was used to select the 120 respondents for this quantitative study, who are Japanese culture enthusiasts in Purwakarta who have previously attended similar events. The data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The findings demonstrate that service quality has a substantial positive impact on purchase intention, while price and location have a considerable negative impact. The results also demonstrate that price, location, and service quality have a significant impact on purchase intention (F = 27.388; Sig < 0.001). These results emphasize the necessity to evaluate ticket pricing strategies and event venue selection in addition to improvements and evaluations of service quality in order to boost buy intention for Japanese cultural event tickets.